The use of ecologically safe means in the protection against sucking phytophages in the ampelocenoses of the Northern Black Sea region - Baranets, L.; Balan, G.; Mezernyuk, T.; Perepelitsa, O. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2024)
Goal. To provide data on insecticides for protection of grapes from thrips and Japanese grape cicada and their influence on the number of entomophages, which is an important element for the organization of effective and environmentally friendly technology of grape growing. Methods. Combination of quantitative and qualitative methods in plant protection — entomology and biomethod. The use of generally accepted methods of analysis (hypothesis, experiment, induction and synthesis) provides sufficient information on the control of grape thrips and Japanese grape cicada under the conditions of using environmentally friendly means of protection, which is one of the main elements of modern technologies for optimizing agroecosystems and obtaining environmentally friendly products. The phytosanitary method of route surveys involves the identification of entomophages and the establishment of dominant species and prevalence of grape thrips and Japanese grape cicada among them. The field method ensures the study of the effectiveness of the elements of the integrated grape crop protection system. The laboratory method involved the identification of species diversity of beneficial fauna. The statistical method was used to calculate the data obtained, determine their accuracy and reliability. Results. The database was updated with environmentally safe products, and regulations for their use were established, which are focused not so much on pest control as on the overall optimization of the phytosanitary condition of plantations, obtaining environmentally friendly products and preserving beneficial fauna. Under natural conditions, without pesticide pressure, the number of predators in a multicomponent entomocomplex is many times higher than in traditional agrocenoses. Conclusions. The composition of preparations with a given direction of minimizing damage to beneficial fauna and, accordingly, the environment was formed. The results obtained and the conclusions formulated on their basis are of practical importance in terms of the prospects for the production of environmentally friendly products by applying environmentally friendly and effective methods of controlling the number of sucking pests and preserving the natural agrobiocenosis.